Development of an Antioxidant Functional Beverage from Soursop Leaves (Annona muricata) and Stevia Leaves (Stevia rebaudiana) for Diabetes Prevention - Jojor Indriani Samosir; Hotnida Sinaga; Eko Kornelius (Postgraduate, University of Mataram, 2026)
Diabetes mellitus is a degenerative disease closely associated with oxidative stress, with a high prevalence in Indonesia reaching 19.5 million cases in 2021. Stevia leaves and soursop leaves have an antioxidant composition with the ability to protect humans from free radicals and prevent oxidation. Soursop leaves and stevia leaves are one contain bioactive compounds with antioxidant and antihyperglycemic properties, making them potential ingredients for functional beverages. This study aimed to formulate a herbal tea combining soursop and stevia leaves and to evaluate its bioactive content, product quality, toxicity, and antihyperglycemic effectiveness. Three formulation ratios (75%:25%, 50%:50%, and 25%:75%) and brewing times of 3, 5, and 7 minutes were investigated. The evaluated parameters included total soluble solids, color intensity, pH, total phenolic content, antioxidant activity, sensory characteristics, and heavy metal contamination analyzed using ICP-OES. The best formulation was obtained at a 25%:75% ratio with a brewing time of 7 minutes. The selected product was further assessed for toxicity using the Brine Shrimp Lethality Test (BSLT) and for antihyperglycemic activity in alloxan-induced male mice, with ethical approval No. 1306/KEPK/USU/2025. Data were analyzed using two-way ANOVA followed by Tukey’s test (α = 0.05). The BSLT results showed an LC₅₀ value of 562 ppm, indicating low toxicity. In the antihyperglycemic test, a dose of 5.6 mg/kg body weight resulted in the greatest reduction in blood glucose levels (46.15%). Overall, the herbal tea combining soursop and stevia leaves was found to be safe and demonstrated potential as a functional beverage for diabetes prevention.